Insitu Nasal Gel of Granisetron For Enhancement of Bioavailability Over Oral Delivery: Formulation, Optimization and In-Vivo Evaluation (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The objective of the present work was formulation, optimization and in-vivo evaluation of in-situ nasal gel of granisetron that shows liquid to gel transformation at nasal temperature (32-34°C) and maximum drug release after 4 hr; shows biovailability enhancement over oral delivery. Formulations were prepared using poloxamer PF 127 as gel forming polymer, carbopol as mucoadhesive agent and fulvic acid as penetration enhancer. A Box Benhken Design was used to prepare the experimental batches and Design Expert software for optimization of the formulation. Ex-vivo evaluations were carried out on sheep nasal mucosa and for in-vivo evaluation, rabbits were used. It was observed that optimized formulation showed gelation temperature near 33°C and drug release of 96% after 4hr. Fulvic acid was evaluated as penetration enhancer in this work and showed significant enhancement of drug diffusion across nasal mucosal membrane. Ex-vivo histological evaluation of nasal mucosa treated with optimized formulation showed no significant destructive effects. In-vivo evaluations showed that the plasma level profile of prepared insitu nasal gel was enhanced significantly over oral delivery. The findings suggested that nasal route nasal transmucosal delivery of granisetron can result in enhancement of its bioavailability over oral route.